Unsupervised physical activity interventions for people with COPD: a systematic review and meta-analysis - Paixão, C. (2022)
Introduction and objectives Unsupervised PA interventions might have a role in the management of chronic obstructive pulmonary disease (COPD) but their effectiveness is largely unknown. Thus, we aimed to identify and synthesise data on the effects of unsupervised PA interventions in people with COPD. Material and methods Databases were systematically searched in April 2020, with weekly updates until September 2021. Randomised controlled trials and quasi-experimental studies comparing unsupervised PA with usual care, were included. Primary outcomes were dyspnoea, exercise capacity and physical activity. The effect direction plot was performed to synthesise results. Meta-analysis with forest plots were conducted for the Chronic Respiratory Disease questionnaire – dyspnoea domain (CRQ-D), 6-minute walk distance (6MWD) and incremental shuttle walk distance (ISWD). Results Eleven studies with 900 participants with COPD (68±10 years; 58.8% male, FEV1 63.7±15.8% predicted) were included. All interventions were conducted at home, most with daily sessions, for 8-12 weeks. Walking was the most common component. The effect direction plot showed that unsupervised PA interventions improved emotional function, fatigue, health-related quality of life, muscle strength and symptoms of anxiety and depression. Meta-analysis showed statistical, but not clinical, significant improvements in dyspnoea (CRQ-D, MD=0.12, 95% CI 0.09-0.15) and exercise capacity, measured with 6MWD (MD=13.70, 95% CI 3.58-23.83). Statistical and clinical significant improvements were observed in exercise capacity, measured with ISWD (MD=58.59, 95% CI 5.79-111.39). None to minor adverse events and a high adherence rate were found. Conclusions Unsupervised PA interventions benefits dyspnoea and exercise capacity of people with COPD, are safe and present a high adherence rate. Unsupervised PA interventions should be considered for people with COPD who cannot or do not want to engage in supervised PA interventions or as a maintenance strategy of PA levels.